Peningkatan Pelayanan PMB Berbasis Android di Politeknik Harapan Bersama Tegal - Arfan Haqiqi Sulasmoro; Arif Rakhman; Nurohim (Politeknik Negeri Cilacap, 2020)
Currently the development of information and communication technology has been approved by the aspects of human life, undeniable in the field of education including the development of mobile technology that presents SmatPhone in various functions that are not only as a means of communication, but also use today's information sources. This creates greater public demand for information on education and encourages Educational Institutions including the Harapan Bersama Tegal Polytechnic to use it as an information media and to register prospective new students based on Android. This study takes the theme